ANALISIS KEBIJAKAN REHABILITASI LAHAN MELALUI PEMBANGUNAN HUTAN RAKYAT PADA CABANG DINAS KEHUTANAN WILAYAH I BOGOR: Analysis of Land Rehabilitation Policy through Community Forest Development Program at the Regional Forestry Branch Office of Bogor (Jurnal ForestrIndo, 2025)
The increasing rate of land degradation in West Java has led to the expansion of critical land areas, which in turn threatens environmental sustainability. One of the strategic efforts to address this issue is through Forest and Land Rehabilitation (FLR) programs, particularly by promoting community-based forest development or "Hutan Rakyat" outside designated forest areas. This study aims to analyze the policy strategies for rehabilitating critical land outside forest areas through community forest development in the jurisdiction of the Forestry Branch Office Region I of West Java Province. The research employs SWOT analysis to identify internal strengths and weaknesses, as well as external opportunities and threats influencing the effectiveness of the policy. Findings reveal various supporting factors, such as government funding, the presence of forest farmer groups, and available guidelines, alongside constraints including unclear land tenure status, limited technological adoption, and insufficient data accuracy. The analysis suggests a combination of strategic approaches, including collaboration with Jakarta's government, engagement of youth, partnerships with academics, and the establishment of legal frameworks to ensure sustainability. These strategies are expected to enhance the effectiveness and efficiency of critical land rehabilitation efforts and contribute to environmental conservation and rural development.